5-Bromoprotocatechualdehyde Combats against Palmitate Toxicity by Inhibiting Parkin Degradation and Reducing ROS-Induced Mitochondrial Damage in Pancreatic β-Cells - Seon-Heui Cha; Chunying Zhang; Soo-Jin Heo; Hee-Sook Jun (MDPI AG, 2021)
Pancreatic β-cell loss is critical in diabetes pathogenesis. Up to now, no effective treatment has become available for β-cell loss. A polyphenol recently isolated from Polysiphonia japonica, 5-Bromoprotocatechualdehyde (BPCA), is considered as a potential compound for the protection of β-cells. In this study, we examined palmitate (PA)-induced lipotoxicity in Ins-1 cells to test the protective effects of BPCA on insulin-secreting β-cells. Our results demonstrated that BPCA can protect β-cells from PA-induced lipotoxicity by reducing cellular damage, preventing reactive oxygen species (ROS) overproduction, and enhancing glucose-stimulated insulin secretion (GSIS). BPCA also improved mitochondrial morphology by preserving parkin protein expression. Moreover, BPCA exhibited a protective effect against PA-induced β-cell dysfunction in vivo in a zebrafish model. Our results provide strong evidence that BPCA could be a potential therapeutic agent for the management of diabetes.